Emerging Strategies in Polyethylene Terephthalate Hydrolase Research for Biorecycling - Kawai, Fusako (ChemSusChem, 2021)
The research on polyethylene terephthalate (PET) hydrolyzing enzymes started in 2005; several studies are now nearing the objective of their application in biorecycling of PET, which is an urgent environmental issue. The thermostability of PET hydrolases must be higher than 70 °C, which has already been established by several thermophilic cutinases, as higher thermostability results in higher activity. Additionally, pretreatment of waste PET to more enzyme‐attackable forms is necessary for PET biorecycling. This Minireview summarizes research on enzymatic PET hydrolysis from two viewpoints: 1) improvement of PET hydrolases by focusing on their thermostabilities by mutation of enzyme genes, their expression in several hosts, and their modifications; and 2) processing of waste PET to readily biodegradable forms. Finally, the outlook of PET biorecycling is described. PET project: Pretreatment of waste polyethylene terephthalate (PET) is requisite for practical realization of enzymatic PET treatment. Amorphized and micronized PET is more susceptible to PET hydrolase attack. PET hydrolase must be thermostable at higher than 70 °C for a certain period of time (preferably ≤10 h). Recycling and upcycling are dependent on the state of waste PET such as purity, single use, mixed use, and how they work together.